The role of personal values in information search strategies for community-based tourism – a study of homestays in Malaysia - Gan, Siew Wei (2023)
The growth of international tourist arrivals in the developing and emerging economies has made it a main contributor of export in services and over 100 million jobs in small and medium sized enterprises. However, it also creates a threat to the social and cultural fabric of the communities involved in the industry and to the environment. Community-based tourism such as the Homestay Programme in Malaysia can be leveraged as a means of conservation of the social, cultural and environmental heritage of these communities. However, the uptake of community-based tourism in Malaysia is developing slower than anticipated.